Circulative Transmission of Cileviruses in Brevipalpus Mites May Involve the Paracellular Movement of Virions - Tassi, Aline Daniele; Ramos-González, Pedro Luis; Sinico, Thais Elise; Kitajima, Elliot Watanabe; Freitas-Astúa, Juliana (Frontiers in Microbiology, 2022)
Plant viruses transmitted by mites of the genus Brevipalpus are members of the genera Cilevirus, family Kitaviridae, or Dichorhavirus, family Rhabdoviridae. They produce non-systemic infections that typically display necrotic and/or chlorotic lesions around the inoculation loci. The cilevirus citrus leprosis virus C (CiLV-C) causes citrus leprosis, rated as one of the most destructive diseases affecting this crop in the Americas. CiLV-C is vectored in a persistent manner by the flat mite Brevipalpus yothersi. Upon the ingestion of viral particles with the content of the infected plant cell, virions must pass through the midgut epithelium and the anterior podocephalic gland of the mites. Following the duct from this gland, virions reach the salivary canal before their inoculation into a new plant cell through the stylet canal. It is still unclear whether CiLV-C multiplies in mite cells and what mechanisms contribute to its movement through mite tissues. In this study, based on direct observation of histological sections from viruliferous mites using the transmission electron microscope, we posit the hypothesis of the paracellular movement of CiLV-C in mites which may involve the manipulation of septate junctions. We detail the presence of viral particles aligned in the intercellular spaces between cells and the gastrovascular system of Brevipalpus mites. Accordingly, we propose putative genes that could control either active or passive paracellular circulation of viral particles inside the mites.